A new Paypayrola (Violaceae) from Panama, with notes about the species complexes for the genus - Ballard, Harvey E. (Jr.) (Phytotaxa, 2022)
A new species of Paypayrola is described from multiple exsiccatae from west-central and east-central Panama. Paypayrola panamensis sp. nov. is represented by dozens of herbarium specimens from 26 putatively distinct populations located at lower elevations on the northern slope, in wet evergreen tropical forest on slopes and ridgetops, as well as along streams and rivers. By in its moderately short-petiolate leaves and yellow corollas, the new species resembles northern South American P. guianensis and P. hulkiana. It differs from P. guianensis in its proportionally longer leaf blades, subsessile to short-pedunculate, short inflorescences, and puberulent sepals longer than broad. It differs from P. hulkiana in its proportionally broader leaf blades, and proportionally broader elliptical to suborbicular sepals, commonly with two (rarely four) distinct lateral nerves besides the medial nerve, and a broadly rounded to frequently truncate or retuse apex. The new species also differs from both in its larger leaf blades with more lateral nerves, tapering to a narrowly rounded or weakly subattenuate apex, and a more densely flowered inflorescence. A key differentiating it from other species of Paypayrola is provided. In discussing the genus, three species complexes are well separated based on corolla color and inflorescence features.